Penyusunan Bahan Ajar Praktikum Akuntansi Lembaga/Instansi Pemerintah Pada SMKS Maitreyawira Tanjungpinang - Muhammad Taufik; Silvyani Silvyani (ConCEPt - Conference on Community Engagement Project, 2021)
This community service (PKM) activity is carried out with the aim of helping one of the schools in Tanjung Pinang in compiling digital teaching materials that are in accordance with school needs so that they can be applied in online learning activities. The partner of this activity is SMK Maitreyawira Tanjung Pinang. Previously, SMK Maitreyawira Tanjung Pinang did not yet have digital teaching materials. This makes the learning process ineffective because it does not have digital teaching materials to make it easier for teachers to deliver learning materials online. This activity is designed to help with the school's problems. This PKM activity is carried out by means of observation and online interviews. Digital teaching materials compiled using Microsoft Power Point. The output produced from this digital teaching material is in the form of digital teaching materials per basic competency along with modules with learning materials and practice questions. The implementation stage consists of three stages, namely the introductory stage of the preparation of digital teaching materials, the provision of digital teaching materials, and the feedback process from the school. Digital teaching materials have been implemented well and can provide improvements in digital teaching materials for schools.